Mycotoxin Challenge in Dairy Cows: Assessment of the Efficacy of an Anti-Mycotoxin Agent by Adopting an In Vitro Rumen Simulation Method - Erica Fiorbelli; Marco Lapris; Michela Errico; Antonella Della Badia; Insaf Riahi; Gabriele Rocchetti; Antonio Gallo (Toxins)
To protect ruminants from the harmful effects of mycotoxins, anti-mycotoxin agents can be added to the dietary ration, thus guaranteeing animal health and production. Therefore, the objective of this study was to evaluate the in vitro ruminal initial sequestration (weak binding) and subsequent desorption (strong binding) of an anti-mycotoxin agent based on a mixture of adsorbing material, turmeric and milk thistle extracts and yeast-based components to adsorb or bio-convert aflatoxins (AF), fumonisins B1 and B2 (FB), trichothecene deoxynivalenol (DON), T-2 and HT-2 toxins, and zearalenone (ZEN). Two doses were tested: Dose 1 simulated 30 mg/cow/d, while Dose 2 simulated 90 mg/cow/d of the anti-mycotoxin agent. Each treatment involved three analytical replicates at each of three incubation times (1, 4, and 24 h post-incubation), with two independent experimental runs providing experimental replicates. Analytical methods, including UHPLC-HRMS and multivariate analyses, were used to both quantify mycotoxin concentrations and reveal dose-dependent reductions, with statistical validations indicating significant changes in mycotoxin levels across both dose and time. The results indicated that the anti-mycotoxin agent was able to highly bind AFB1, T2, and HT-2 toxins since its concentration was always under the limit of detection (<1 ppb). Regarding ZEN (weak binding mean: 94.6%; strong binding mean: 62.4%) and FBs (weak binding mean: 58.7%; strong binding mean: 32.3%), orthogonal contrasts indicated that the anti-mycotoxin agent was able to effectively bind these toxins using Dose 1 (p < 0.05). This finding suggests that Dose 1 may be sufficient to achieve the targeted effect and that a further increase does not significantly improve the outcome. Regarding DON, a strong linear relationship was observed between dose and adsorption. However, the complex interactions between the mycotoxin, the ruminal environment, and the anti-mycotoxin agent made it difficult to establish a clear dose–effect relationship (p > 0.10). UHPLC-HRMS analysis identified over 1500 mass features in rumen samples, which were further analyzed to assess the effects of the anti-mycotoxin agent. Hierarchical clustering analysis (HCA) revealed significant changes in the untargeted metabolomic profiles of samples treated with mycotoxins compared to control samples, particularly after 24 h with the anti-mycotoxin treatments. Clear differences were noted between strong binding and weak binding samples. Further analysis using orthogonal partial least squares discriminant analysis (OPLS-DA) highlighted distinct metabolomic profiles, with stronger predictive ability in the strong binding group (Q2 cumulative value of 0.57) compared to the weak binding group (0.30). The analysis identified 44 discriminant compounds in the strong binding model and 16 in the weak binding model. Seven compounds were common to both groups, while silibinin, known for its antioxidant and anti-inflammatory properties, was found among the unique compounds in the weak binding group. Overall, the findings suggest that both doses of the anti-mycotoxin agent significantly influenced the chemical profiles in the rumen, particularly enhancing the binding of mycotoxins, thereby supporting the role of phytogenic extracts in mitigating mycotoxin effects.